Evaluation of herbal leaf meal as an alternative to in-feed antibiotics on haematological parameter and serum biochemical indices of growing sexed pigs - O, ADEGUN W; P, NJOKU C; A, EKUNSEITAN D; M, AGBAJE (The Indian Journal of Animal Sciences, 2023)
This study was conducted at the Federal University of Agriculture, Abeokuta in September 2019 to evaluate the influence of sex and sole or combined herbal leaf meal as alternative in-feed antibiotics on serum biochemical indices. A total of thirty large white sexed pigs of eight weeks were allotted into five (5) dietary treatments for 12 weeks. Dietary treatments had no significant effect on haematological parameters and serum biochemical indices. Sex did not influence the haematological and serum biochemical profile of pigs except for monocyte, albumin, aspartate aminotransferase, and cholesterol respectively. Dietary supplementation did not influence the haematological serum biochemical profile of pigs. This indicates that the haematological indices were not influenced by sex and diet except the significant values which were within the normal range for sexed pigs which reveals that sex and diet does not compromise the immune system of the sexed pigs.